Contract farming and commercialization of agriculture in developing countries - Glover, David (International Food Policy Research Institute, 1994)
The distributional benefits of commercialization of agriculture, access to commercialization opportunities, and sharing of commercialization risks are functions of institutional arrangements. Obviously, the indirect food security and nutritional effects are, thereby, partly a function of such institutional arrangements. This chapter explores the relevance to food security of one form of contractual relationship in agriculture: formal contracts between producers and buyers (generally processors or exporters), a production and marketing system known as contract farming. The chapter does not refer to the extensive literature on informal contractual relations, such as sharecropping, or on traditional systems of contract farming, such as the extensive "strange farmer" system in West Africa's groundnut sector. The chapter draws generalizations and conclusion from studies done by the author and by other researchers. The latter include two research networks initiated by the author. One network surveyed the experience with contract farming in several East and Southern African countries (Eastern Africa Economic Review 1989); the second examined the experience in Thailand, Malaysia, and the Philippines (Glover and Lim, forthcoming).